A Preliminary Earthquake Detection from The Seismic Temporary Network in The Opak Fault. Issue 1 (1st September 2022) - Simanjuntak, Andrean V H; Saragih, Naikson Fandier; Anshori, Muhajir; Sinambela, Marzuki; Razi, Ar; Muksin, Umar; Simangunsong, Afryanti V; Sihotang, Noviana; Asnawi, Yusran; Jaya, Indra Kelana
Abstract: Microseismic observation is a mandatory tool for analysing and imaging the progress of source earthquake mechanism. The observation of low-quality signal is usually found because of false detection, transient signals by natural noise, or related to seismometer condition and some human activities. Therefore, we try to figure the microseismic phenomenon after major earthquake in the Jogjakarta fault that was generated by an active fault namely Opak Fault. We used the seismic data recording from the seismic project that was installed in 2006 cover the Jogjakarta region. We used one week data to see the potential detection and highlight the possible of positive or negative false detection. With total 16 stations, we got 500 events in only one week recording. We used a various threshold with 110 to scan all the dataset and we obtained 450 events with 50-100 events with possible of false positives. Meanwhile, the threshold of 112 has < 50 events that could be suitable with the waveforms. The example results of 120 thresholds figure a strong event that is located by highly resolution of stack coherent from some stations with precise of P and S phase fitting. This study present the first automatic earthquake locations that can provide more detail of seismic structure information in the Jogjakarta region.